Visual discourse of urban space: a semiotic analysis of street art and linguistic graffiti in Jakarta - Dedy Sartono (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Jakarta’s urban landscape has evolved into a contested discursive space where street art, graffiti, and murals serve as multimodal forms of social commentary, identity expression, and political resistance. Objective: This study aims to examine how signs, symbols, spatial placement, and layered authorship in Jakarta’s street art construct and negotiate urban narratives. Method: Using a qualitative multimodal approach—integrating Semiotic Analysis, Visual Discourse Analysis, and Critical Discourse Analysis—the research analyzes purposively sampled artworks documented through fieldwork, community archives, and digital platforms. Results: The findings reveal three core patterns: first, minimalist monochromatic murals function as coded endurance strategies under conditions of censorship; second, infrastructural murals on flyovers reframe utilitarian structures as civic discourse platforms; third, layered graffiti walls operate as participatory archives, allowing marginalized voices to engage in iterative public dialogue. Collectively, these patterns demonstrate how Jakarta’s street art simultaneously embodies resilience, cultural memory, and political agency. Implication: The implications underscore the need to recognize street art as a critical urban semiotic infrastructure, informing both scholarly discourse and inclusive cultural policy. Novelty: This study demonstrates how multimodal street art practices transform urban space into a dynamic discursive arena where resilience, collective memory, and political agency are continuously negotiated through visual and spatial meaning-making.